Sucide Attempt in Acute Psychoic Conditions from Biopsychosicial Management Review - Meilaniwati Sarfa; Melati Wahyurini; Era Catur Prasetya (Jurnal Psikiatri Surabaya, 2021)
Acute psychotic and transient disorders have annually increased, especially in developing countries. The highest prevalence for acute Psychotic disorders is currently in three developing countries, namely Ibadan, Nigeria, and India. Reported the most causes by psychosocial factors and biological factors. Acute and Transient Psychotic disorders have an annual incidence rate of about 3.9% to 9.6% of the 100.000 population. The reported prevalence range from 10% to 50% mostly in the first year. We aim to report a case of Acute and Transient Psychotic Disorders accompanied by suicide attempts to increase cases so that psychiatrists should be able to make a diagnosis quickly and precisely because it is included in the emergency psychiatric. Acute and Transient Psychotic Disorders often cause symptoms in the form of acts of self - harm or others, in the form of committing suicide, which is a very important social phenomenon and requires attention not only from a psychiatrist but also the general public. The phenomenon of suicide has spread to almost all parts of the world, both in countries with advanced technology and in developing countries. Integrated management of this case is clinically oriented to a biopsychosocial model that is used as a basic principle in the clinical practice of a doctor in building relationships with patients. In this case, we reported a 24 – year - old male, the first attack, occurring within one week, and accompanied by suicidal thoughts. So it is necessary to take a biopsychosocial approach that aims for comprehensive and sustainable interventions.